2022
DOI: 10.1126/science.abm0717
|View full text |Cite
|
Sign up to set email alerts
|

TaCol-B5 modifies spike architecture and enhances grain yield in wheat

Abstract: Spike architecture influences grain yield in wheat. We report the map-based cloning of a gene determining the number of spikelet nodes per spike in common wheat. The cloned gene is named TaCOL-B5 and encodes a CONSTANS-like protein that is orthologous to COL5 in plant species. Constitutive overexpression of the dominant TaCol-B5 allele but without the region encoding B-boxes in a common wheat cultivar increases the number of spikelet nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 49 publications
0
49
1
Order By: Relevance
“…BBX is a transcription factor of zinc finger protein, which plays a prominent role in plant growth and development, hormone response, and stress tolerance [ 54 ], but the function of BBX genes in tobacco has not been studied. In this study, the phylogeny, gene structure, cis-acting element, and expression pattern under diverse conditions of the NtBBX genes were comprehensively analyzed in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…BBX is a transcription factor of zinc finger protein, which plays a prominent role in plant growth and development, hormone response, and stress tolerance [ 54 ], but the function of BBX genes in tobacco has not been studied. In this study, the phylogeny, gene structure, cis-acting element, and expression pattern under diverse conditions of the NtBBX genes were comprehensively analyzed in tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…The haplotype H5 was slightly sensitive to photoperiod in the 83B28 and A5302 backgrounds; the underlying mechanism deserves further investigation. In wheat, the CCT domain gene TaCol-B5 also has pleiotropic effects: It increases the number of spikelet nodes per spike, as well as the number of tillers and spikes, leading to increased grain yield ( Zhang et al, 2022 ). CCT domain genes have obvious convergent effects in rice ( Ghd7 ), maize ( ZmCCT ), and wheat ( TaCol-B5 ), all of which are pleiotropic genes that regulate plant growth, development, stress responses, yield performance, and other agronomic traits ( Xue et al, 2008 ; Weng et al, 2014 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Induced novel mutations were also detected on other genes, such as TaTB1, TaQ, WFZP, Ms1, TaNAC019, TaCol-B5, and TaGW2, etc. (Dobrovolskaya et al, 2015;Wang et al, 2017b;Dixon et al, 2018;Li et al, 2019;Liu et al, 2020a;Zhang et al, 2022;Zhang et al), among which many mutation sites have not been reported before (Table S4). Thus, the generated KN9204 EMS-mutagenesis library contains novel allelic variations on yield and agronomical-traits related crucial genes and holds the potential for future breeding applications.…”
Section: Identification Of Gene-index Mutations In Kn9204 Mutant Librarymentioning
confidence: 99%